Reduction of leucocyte cell surface disulfide bonds during immune activation is dynamic as revealed by a quantitative proteomics workflow (SH-IQ). Issue 9 (19th September 2018) - Stegmann, Monika; Barclay, A. Neil; Metcalfe, Clive
Abstract : Abstract : Communication through cell surface receptors is crucial for maintaining immune homeostasis, coordinating the immune response and pathogen clearance. This is dependent on the interaction of cell surface receptors with their ligands and requires functionally active conformational states. Thus, immune cell function can be controlled by modulating the structure of either the receptor or the ligand. Reductive cleavage of labile disulfide bonds can mediate such an allosteric change, resulting in modulation of the immune system by a hitherto little studied mechanism. Identifying proteins with labile disulfide bonds and determining the extent of reduction is crucial in elucidating the functional result of reduction. We describe a mass spectrometry-based method—thiol identification and quantitation (SH-IQ)—to identify, quantify and monitor such reduction of labile disulfide bonds in primary cells during immune activation. These results provide the first insight into the extent and dynamics of labile disulfide bond reduction in leucocyte cell surface proteins upon immune activation. We show that this process is thiol oxidoreductase-dependent and mainly affects activatory (e.g. CD132, SLAMF1) and adhesion (CD44, ICAM1) molecules, suggesting a mechanism to prevent over-activation of the immune system and excessive accumulation of leucocytes at sites of inflammation.